(untitled) (Medico Legal Update, 2020)
Background: Hypertension endangering a risk of cardiovascular events and BP reduction will reduce such complications. the role of aspirin in hypertension is debated, however it is advised in primary prevention in case of patient with high risk factors assessed by one of the cardiovascular risk calculator, a state in which the benefit of aspirin outweigh the risk of complications. Objectives: Estimate the prevalence of aspirin misuse in hypertensive patients ,which population at risk and estimate the possible source of this misuse habit. Patients and Methods: A cross sectional study that has been conducted in babil city major hospitals for the period from the 20th of January to 2nnd of May. our study sample included 353 patients all cases were between 35 to 75 years old who attend to internal medicine outpatient clinic , emergency departments and inpatients of the above hospitals . All patient had hypertension being treated with antihypertensive agents and they did not experience any vascular events like CVA, IHD and PVD. Results: 30.59% of patient do not use aspirin and 64.31 % of patients use aspirin prescribed by doctors. Most of aspirin use was according to doctor advice( 92.7%). 5.1 a use aspirin by advice from others. Aspirin use was more with increased age group (p value 0.003) and in females( p value is 0.04). No significant differences between educational level, economic status, residency and occupation with the use of aspirin. Regarding aspirin intake by their doctors and score <10 %: women were more than men ,age 40 – 60 years. Mostly were urban, higher education of 50% had positive history of CVD. Patient who need aspirin but they didn’t use aspirin, were 66 patients mostly male live in urban area higher education , smoker , most of them had no family history of cardiovascular diseases. Conclusion: Aspirin use requires coordinated interaction between patient and physician with encouraging the importance patient education about aspirin use, side effects and CVD risk and proper evaluation of patients risk factors and stratification using simplified charts accessible in health centers.